White glue intoxication in a plain parakeet (Brotogeris tirica) – Case report (Research, Society and Development, 2022)
Despite the lack of information on avian sensitivity to toxic agents, it is known that several products that are relatively harmless to humans may have profound effects on birds. Thus, the objective of this work is to report the case of a plain parakeet (Brotogeris tirica) that was intoxicated after ingesting white glue and to discuss the pathophysiological aspects involved in intoxication. For this, the case study methodology was used, with a qualitative character, describing the case in detail and posteriorly seeking subsidies in the literature centered on the subject under study to complement the knowledge necessary to carry out this study. Twelve hours after ingesting white glue, the plain parakeet (Brotogeris tirica) began to experience recurrent vomiting episodes, which rapidly progressed to a critical condition of dyspnea, prostration and death. Although Polyvinyl Acetate (PVAc), the main component of that type of glue, is described as a non-hazardous substance, necroscopic and histopathological findings, consisting of pulmonary and hepatic congestion and hemorrhage, were very similar to that seen in some avian toxicoses. A thorough review on in vivo and in vitro mechanisms of PVAc degradation suggests that an association of high-dose exposition and B-esterase insufficiency in birds was the probable cause of PVAc poisoning, serving as an alert to veterinarians and bird owners.